Investigation of materials and damage sources of local masonry structures in Turkey - Zengin, B.; Bulduk, M.; Aydin, E.; Kosar, E.; Altay, A. Z. (WIT PRESS, 2013)
Masonry buildings are preferred for reasons such as their ease of production, low cost and of obtaining materials. While these materials are preferred in rural areas due to their low cost, they are also an option in urban regions. The majority of the buildings in Turkey's rural regions consist of masonry buildings, with materials being obtained locally. However, almost none of these buildings exhibit earthquake resistance. Masonry buildings that have been damaged in recent earthquakes throughout Turkey support this argument. In this paper, earthquake damage to masonry buildings built using locally obtained materials, the material properties, and the architectural and load-bearing systems of these buildings were investigated and the sources of damage were determined.
Keywords: masonry building; stacked material; earthquake; Engineering; Geology